SEXY CHINKIES IN INDIAN CITIES: CAN WE EMBRACE A SLANT-EYED MARY? - I. Aye (Acta Theologica)
This article investigates the escalation of anti-northeastern racism during the COVID-19 pandemic in India, by analysing the existing and underlying forms of domination faced by north-eastern Indian populations living in the metropolitan cities of India. It particularly investigates the intersectionalities of caste and race, gender, LGBT, and the older form of anti-Chinese sentiment called the yellowperil myth. It explores Mary Magdalene’s life and reflects on the public and cultural narrative, while simultaneously highlighting the lived experiences of north-eastern women in Indian cities. The article compares the experience of Mary Magdalene with that of the indigenous northeastern women. It asks how Mary, if she were slant-eyed, negotiated the humiliation and discrimination of race and gender, and how the figure of Mary can help challenge the public myth and offer a site of resistance for north-eastern women, many of whom are Christian.